The bankruptcy of a private investor in a project of public-private partnership - F. S. Rastegaeva (Путеводитель предпринимателя)
The article presents an analysis of the interaction between private companies and the government to resolve social and economic problems and to achieve mutual objectives. In particular the difficulties encountered in the implementation of PPP projects due to the bankruptcy of a private party.